The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.3109/10903127.2015.1115928
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Use of Emergency Medical Services: The Role of Chronic Illnesses and Behavioral Health Problems

Abstract: Objective The increasing use of prehospital emergency medical services (EMS) and its contribution to rising emergency department use and healthcare costs point to the need for better understanding factors associated with EMS use to inform preventive interventions. Understanding patient factors associated with pediatric use of EMS will inform pediatric-specific intervention. We examined pediatric patient demographic and health factors associated with one-time and repeat use of EMS. Methods We reviewed data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 45 publications
0
28
1
Order By: Relevance
“…It is unclear if the incidence of pediatric diabetic issues is low or if these patients were being informally directed towards the pediatric centre. Knowlton et al previously demonstrated that chronic medical conditions, such as diabetes, are linked to increased ambulance usage, but there are no published studies examining whether these patients benefit from specialized care [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear if the incidence of pediatric diabetic issues is low or if these patients were being informally directed towards the pediatric centre. Knowlton et al previously demonstrated that chronic medical conditions, such as diabetes, are linked to increased ambulance usage, but there are no published studies examining whether these patients benefit from specialized care [4].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of adolescents visiting EDs in the United States found a sixfold increase in the odds of transfer or admission for those presenting with mental health complaints. Further study may be of benefit since pediatric patients with mental health and substance abuse have a higher proportion of repeat EMS usage [4].…”
Section: Discussionmentioning
confidence: 99%
“…The high number of emergency medical service (EMS) calls coupled with subsequent high ED utilization to address patients’ behavioral health concerns have been well documented [ 4 - 7 ]. Regarding pediatric EMS use, chronic somatic conditions and behavioral health problems appear to contribute to a large proportion of the repeat pediatric EMS use [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given their role as a significant entry point into the broader health services, utilisation of the emergency medical services has been suggested as a potential solution to partly improve access to specialised mental health services (8)(9)(10)(11). There is, however, limited evidence to indicate that this increase in caseload is likely to be considerable, with the potential to significantly impact service delivery, quality of care, and patient safety (8)(9)(10)(11). This is further confounded by concerns that mental health emergencies have not historically constituted what could be considered a "traditional" case type serviced by or exposed to EMS, such as myocardial infarction, stroke, or respiratory emergencies (10).…”
Section: Introductionmentioning
confidence: 99%
“…Given their role as a significant entry point into the broader health services, utilisation of the emergency medical services has been suggested as a potential solution to partly improve access to specialised mental health services (8)(9)(10)(11). There is, however, limited evidence to indicate that this increase in caseload is likely to be considerable, with the potential to significantly impact service delivery, quality of care, and patient safety (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%